Synthesis and Biological Evaluation of Novel Anthranilic Diamides Containing N-H/CH3-1H-Pyrazole - Zhang, Xiulan; Zhang, Huan; Liu, Jingbo; Xiong, Lixia; Li, Zhengming (Chemical research in Chinese universities, 2020)
In order to systematically study the structure-activity relationship of anthranilic diamides and develop insecticides with simple structure and high efficiency, a series of novel anthranilic diamides containing N -H/CH 3 -1 H -pyrazole was designed and synthesized. Their chemical structures were characterized by 1 H NMR spectra, high resolution mass spectrometry(HRMS) or 13 C NMR spectra. The preliminary bioassay results indicated that all title compounds displayed moderate insecticidal activity against oriental armyworm( Mythimna separata ) at 200 mg/L and fungicidal activities against six kinds of fungi at 50 mg/L, especially compound 5 i showed 50% insecticidal activity at 25 mg/L. In addition, some compounds exhibited certain antitumor activities. It was demonstrated that the introduction of CH 3 group into pyrazole ring was superior to H for the insecticidal activity.